Mirage of Police Reform : Procedural Justice and Police Legitimacy - Worden, Robert E.; McLean, Sarah J., 1971- (Book collections on Project MUSE., 2017)
"In the United States, the exercise of police authority--and the public's trust that police authority is used properly--is a recurring concern. Contemporary prescriptions for police reform hold that the public would trust the police more and feel a greater obligation to comply and cooperate if police-citizen interactions were marked by higher levels of procedural justice by police. In this book, Robert E. Worden and Sarah J. McLean argue that the procedural justice model of reform is a mirage. From a distance, procedural justice seems to offer relief from strained police-community relations. But a closer look at police organizations and police-citizen interactions shows that the relief offered by such reform is, in fact, illusory"--Provided by publisher